53=6x-1

Simple and best practice solution for 53=6x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 53=6x-1 equation:


Simplifying
53 = 6x + -1

Reorder the terms:
53 = -1 + 6x

Solving
53 = -1 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
53 + -6x = -1 + 6x + -6x

Combine like terms: 6x + -6x = 0
53 + -6x = -1 + 0
53 + -6x = -1

Add '-53' to each side of the equation.
53 + -53 + -6x = -1 + -53

Combine like terms: 53 + -53 = 0
0 + -6x = -1 + -53
-6x = -1 + -53

Combine like terms: -1 + -53 = -54
-6x = -54

Divide each side by '-6'.
x = 9

Simplifying
x = 9

See similar equations:

| 0=-4+x+0.75x^2 | | X*2+15=11 | | 5m-10-4m-7=0 | | k-8/3=19/3 | | 1600-2Q= | | 3sin(2x+10)=2 | | -2.4+j=-1.8 | | 1700-2Q= | | -10(s+4)=-106 | | Z^4=6z^2+7 | | 5(y+-4)=35 | | 5y+4=35 | | 27=3(2x-3) | | 4-5x+20-6x=68 | | 8x+28=4(x+5) | | -36=8x-11x | | 8(x-10)=-92 | | (x-8)+x+(x+x-8)*0.75=70 | | (x^2+x)-(x+2)=0 | | (1,06²²-1)/(1,06²²,065) | | 7/2x=105 | | 2x+3(4+4)=2x+3(4) | | 422/x=9 | | -10x=10-10 | | Tan-1(8/3)=69.4 | | 2(4x-5)=-38 | | x^2+y^2+4x+5=0 | | 10+(x-1)10=200 | | log^3x=17 | | 6(3n-1)=4(n+4) | | 8+5y=8900 | | 15x-1=9-5x |

Equations solver categories